Analisis Kebutuhan Es dan Dampaknya Terhadap Kualitas Ikan di Pelabuhan Perikanan Samudera Lampulo Banda Aceh - Harits Gunawan; Indra Indra; Faisal Abdullah (Universitas Islam Negeri Ar-Raniry, 2018)
The freshness of fishes caught by fishing vessels must be maintained to preserve the fish quality, which usually using ice as the cooling media. The ice needed depend on the catch amount, vessel capacity, and the temperature. The aim in this study was to analyze the amount of ice needed for fishing vessels and the effect of ice on the quality of fishes caught at the Lampulo Ocean Fisheries Port in Banda Aceh. This research was conducted from May to August 2018, using descriptive method with organoleptic test and simple regression analysis. The result shows that the total amount of ice blocks needed by fishing vessels in the Lampulo Ocean Fishery Port for fishing activities is 11,337 tons / month. The fish quality shows organoleptic scale value of 7 to 8, which mean that the fishes caught in the Lampulo Ocean Fishery Port belong in fresh category. From the results of the Regression analysis can be concluded that the amount of ice carried by fishing vessels for fishing operations have a significant effect on the quality of the fish.